Proses Promosi Melalui Media Sosial untuk Event Genrevolusi oleh Genvoice by PT Koran Jakarta - Sarah Qiptiah Putri; Sudarno Sudarno; Fauzi Mubarak; Yuningsih Yuningsih (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2026)
Social media plays an important role in the lives of Generation Z. As digital natives, they utilize these platforms not only to socialize but also to access information and engage with social and cultural issues. This opens up business opportunities for organizations to interact with them through digital content marketing and relevant campaigns. Genvoice, a media platform that targets young audiences, organized the “GenRevolusi” event to educate and empower Generation Z by combining both digital and offline activities. This study explores the social media promotional strategy implemented by Genvoice for the GenRevolusi event. The researcher was directly involved in content creation, scheduling, publishing, and audience engagement as part of the internship program. Using qualitative methods such as observation, interviews, document analysis, and literature review, this study highlights how planning, visual appeal, and real-time interaction affect reach and engagement. Strong storytelling, consistent branding, and tailored formats help boost visibility, while challenges like limited time, budget, and content adaptation across platforms require strategic planning to ensure meaningful audience involvement.